Listening comprehension problems and strategies among Kurdish EFL learners - Rajab, Saadallah Yaseen; Nimehchisalem, Vahid (English Language Education Publishing, 2016)
This quantitative research investigated listening comprehension problems and strategies usage among Kurdish EFL undergraduates. Additionally, it tested the relationship between the learners’ listening problems and strategy usage. More specifically, the listening problems included input, context, process, affect and task problems while the listening strategies consisted of cognitive, meta-cognitive and socio-affective strategies. Through a survey, a questionnaire was used to elicit data from 165 randomly selected undergraduates in Iraqi-Kurdistan universities. The findings showed that the learners suffered from input and context listening comprehension problems. Meta-cognitive strategy was the major listening strategy used. The relationship between listening problems and strategy usage among the learners was significantly negative and negligible, r= -.186, p < .05. The findings generally imply that it is important for instructors of a second language to take note of the different listening problems that exist among listeners so as to enable them to apply the appropriate strategies.